Islamic financial engineering, its concept, history, fundamentals and principles From an Islamic perspective - جميل علي رسول; صالح نوري حبيب (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Islam, which is a global religion, includes a financial economy and has its characteristics, Serves society and preserves it from collapse, bankruptcy and economic crises if its provisions are observed. Therefore, it contains principles in the field of financial transactions that open the door to those who strive to adapt the developments in the economy, interests and governance behind the legislation of the provisions all this and other things that serve investors in various fields are called financial engineering in the present era, which is a new term but its content and content is as old as Islam. Islam's statement of the taboos proved that the origin in the transactions (Halal), and thus left the space for innovation and creativity in the economy, as well as rationalizing the new issues of money by legislating tricks that do not lead to evils and prohibitions. The ruling is to prohibit them from usury, cheating, bribery, monopolization and gambling, these are the things that threaten the economic systems to disappear, and away from the morality, humanity and equity that Islam ordered to abide by and preserve. All this shows the importance of the existence of financial engineering and development to be present in all related issue by finding solutions derived from the spirit of Islam and its great purposes to prove its reality and validity for all time and place.